Early versus late onset depression: sociodemographic and clinical characteristics - Taher Abdelraheem Sayed; Osama Abd Alreheem Mahmoud; Saber Hadad (Middle East Current Psychiatry, 2022)
Abstract Background Late-onset depression is different from early-onset depression in its sociodemographic and clinical characteristics and risk factors. This study aimed to demonstrate the differences in sociodemographic characteristics as well as clinical presentation between late-onset depression (after the age of 60 years) and early-onset depression (before the age of 45 years) and to determine the sociodemographic risk factors for late onset depression. Fifty-five patients between 18 and 45 years of age (group 1) and 55 patients aged 60 years and above (group 2) diagnosed for the first time with major depressive disorder were compared regarding sociodemographic and clinical characteristics. They were recruited from the psychiatric clinic at Sohag University Hospital. All participants were subjected to a Structured Clinical Interview for DSM-IV (SCID-IV), sociodemographic data form, Beck Depression Inventory-Second Edition (BDI-II), and Apathy Evaluation Scale (AES). Results The patients in group 2 were more commonly single (29%), employed (74.54%), living in rural areas (56.36%), and had high school education (41.81%). While the patients in group 2 were more commonly widows (18.18%), unemployed (61.81%), had less than high school education (47.27%), and had chronic diseases (78.81%). Significant risk factors for late onset depression are being widow, unemployed, having low socioeconomic status, and having a chronic medical disease. Patients with late-onset depression were more commonly presented with apathy, cognitive impairment, and somatic symptoms, as well as sleep disturbance (mean±SD 57±6, 70.9%, 61.81%, and 81.81%, respectively) than early-onset depression (mean±SD 49± 4, 47.27%, 36.36%, and 70.9%, respectively). Conclusions Cases with late onset depression are featured by being unemployed, widow, having low socioeconomic status and low educational level, suffering from a chronic medical condition and living in an urban area. In late onset depression, somatic symptoms, apathy, sleep disturbances, as well as cognitive impairment are prevalent presenting symptoms.